Peran Camat Dalam Koordinasi Administrasi di Kecamatan Barong Tongkok Kabupaten Kutai Barat - Yohanes Liku; Suhardiman Suhardiman; Nanik Pujiastuti (Universitas 17 Agustus 1945 Samarinda, 2020)
The purpose of this study is to find out and describe how the Role of Camat in Coordination of Administration in Barong Tongkok District of West Kutai Regency. This type of research is descriptive qualitative research. To obtain research data, especially with the researcher's interview technique using the Purposive Sampling method, then to obtain valid data, the researcher triangulates the source that allows for researchers to double-check and can complete information from various sources. From the results of the study, it can be concluded that the Role of Camat in Coordination of Administration in Barong Tongkok District of West Kutai Regency is both vertical with related agencies and horizontal administrative coordination with the heads of sections in the Barong Tongkok District Office. From the results of the study, coordination of administrative services of the district government in providing administrative services to the community there are inhibiting factors, namely the lack of facilities in the smooth administrative process such as a long administrative system, lack of professional staff in carrying out their duties and there is one village that has a long distance from the District Office. Supporting factors in providing administrative services to the community are the availability of budgets in the process of improving administrative services and the availability of Daran facilities and infrastructure that support in the process of administrative services to the community.Tujuan dari penelitian ini adalah mengetahui dan menggambarkan bagaimana Peran Camat dalam Koordinasi Adminstrasi di Kecamatan Barong Tongkok Kabupaten Kutai Barat. Jenis penelitian ini adalah penelitian kualitatif deskriptif. Untuk memperoleh data penelitian, khususnya dengan teknik wawancara peneliti menggunakan metode Purposive Sampling, kemudian untuk mendapatkan data yang valid, maka peneliti melakukan triangulasi sumber yang memungkinkan bagi peneliti untuk melakukan pengecekan ulang serta dapat melengkapi informasi dari berbagai sumber. Dari hasil penelitian dapat disimpulan bahwa Peran Camat dalam Koordinasi Adminstrasi di Kecamatan Barong Tongkok Kabupaten Kutai Barat baik bersifat vertikal dengan instansi terkait maupun koordinasi administrasi horisontal dengan kepala seksi-seksi yang ada di Kantor Kecamatan Barong Tongkok. Dari hasil penelitian tersebut, Koordinasi pelayanan administrasi pemerintah Kecamatan dalam memberikan pelayanan administrasi kepada masyarakat terdapat faktor penghambat yaitu kurang tersedianya sarana dalam kelancaran proses administrasi seperti sistem administrasi yang masih panjang, kurang profesionalnya staf dalam menjalankan tugas serta terdapat satu Kelurahan yang memiliki jarak yang jauh dengan Kantor Kecamatan. Faktor pendukung dalam memberikan pelayanan administrasi kepada masyarakat ialah tersedianya anggaran didalam proses meningkatkan pelayanan administrasi dan terdapatnya fasilitas daran dan prasarana yang mendukung dalam proses pelayanan administrasi kepada masyarakat